Recent urban growth and change in the spatial structure of Iranian cities: The case of Tabriz (1966-1991). - Azimi, Nooreddin. (University of Ottawa (Canada), 1996)
This study addresses the process of recent urban growth and change in the spatial structure of the City of Tabriz, Iran over the period 1966-1991. The main objectives are to see how the recent rapid urban development in Tabriz has changed its spatial form and activity patterns and what are the main social and environmental implications of these changes. The research is mainly based on data obtained from various Iranian government agencies combined with additional field work and interviews carried out for this research. Population density model and location quotients (LQ) method are used to analyze the recent change in the population density and land use pattern in Tabriz. An impact analysis is used to assess the social and environmental implications of these urban changes. ARC/INFO, a GIS software, is employed to illustrate the spatial structural changes and part of the spatial analysis in this study. The following results are obtained from this study: (1) Natural population growth and rural-urban migrations caused by land reform, mechanization of agriculture and inappropriate government policies are main factors of recent rapid growth in Tabriz. (2) A dramatic increase in the number of motor vehicles, the decline in the average household size and government interventions have been the major factors for the rapid physical expansion and the overall population density decline in Tabriz over recent decades. However, due to topographic reasons, orientation of main transportation network and zoning policy, the change in density pattern among different areas of the city varies substantially. Whereas the city centre and east-west peripheries, occupied mainly by middle or high income groups, have experienced population density decline, the northern and southern fringes, occupied mainly by low income groups and squatter settlements, have increased their density. (3) The examination of the spatial distribution of land uses reveals a higher degree of concentration and significant change in the geographical location of urban activities within the city. The comparison of the LQ among land uses between 1966 and 1991 shows that educational, industrial and health care land uses are becoming more polarized, whereas transportation and residential land uses, because of their higher proportions compared to the existing developed urban land, are relatively less concentrated. In terms of geographical location, there has been a strong tendency for shifting the industrial activity, public organizations, government and some commercial (especially services) activities from the city centre to the peripheries. (4) The recent urban growth in Tabriz has been associated with the loss of good agricultural lands around the city, residential expansion into hazardous geographical locations and the decay of buildings in the historical sector. Major social implications include more physical segregation among residential groups and the unequal distribution of public services among them.
Keywords: Geography.